2019
DOI: 10.1111/jth.14335
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Shp2 negatively regulates thrombus stability under high shear stress

Abstract: Shp2 negatively regulates thrombus stability under pathological shear rate. Shp2 suppresses TXA2 receptor‐mediated platelet dense granule secretion. Through αIIbβ3 outside‐in signaling, Shp2 targets calmodulin‐dependent activation of Akt. Shp2 may serve to prevent the formation of unwanted occlusive thrombi. Summary BackgroundPerpetuation is the final phase of thrombus formation; however, its mechanisms and regulation are poorly understood. ObjectiveTo investigate the mechanism of Shp2 in platelet function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…It has previously been shown through the use of SHP2 conditional knockout mouse models that platelet SHP2 negatively regulates thrombus stability under pathological shear rate by inhibiting TXA2 and aIIbb3 outside-in signaling-dependent platelet activation. 23,24 We did not, however, find thrombus instability of NS platelets under high shear stress or defects in U46619induced platelet aggregation. The difference between our data and the previous 2 studies 23,24 may be due to the loss of adaptor properties of SHP2, in addition to catalytic activity in SHP2deficient mouse models, or possible dominant-negative effects in SHP2 gain-of-function mice.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It has previously been shown through the use of SHP2 conditional knockout mouse models that platelet SHP2 negatively regulates thrombus stability under pathological shear rate by inhibiting TXA2 and aIIbb3 outside-in signaling-dependent platelet activation. 23,24 We did not, however, find thrombus instability of NS platelets under high shear stress or defects in U46619induced platelet aggregation. The difference between our data and the previous 2 studies 23,24 may be due to the loss of adaptor properties of SHP2, in addition to catalytic activity in SHP2deficient mouse models, or possible dominant-negative effects in SHP2 gain-of-function mice.…”
Section: Discussioncontrasting
confidence: 54%
“…23 In addition, SHP2 negatively regulates thrombus stability under pathological shear rate by acting downstream of thromboxane A2 (TXA2)/TP receptor and regulating the outside-in aIIbb3 integrin signaling. 24 To determine whether increased SHP2 activity may be responsible for a thrombopathy related to a signaling defect, we explored platelet responses in 10 NS patients carrying heterozygous PTPN11 mutations and in a well-characterized mouse model of NS expressing the heterozygous D61G mutation of the Ptpn11 gene (Ptpn11 D61G/1 ). 25 Another RASopathy clinically related to NS is NS with multiple lentigines (NSML), previously referred to as LEOPARD syndrome (according to the acronym: multiple Lentigines, ECG conduction abnormalities, Ocular hypertelorism, Pulmonic stenosis, Abnormal genitalia, Retardation of growth, and sensorineural Deafness).…”
Section: Introductionmentioning
confidence: 99%
“…PECAM-1 can also trigger the internalization of GPIb [138]. Recently, G6B and carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM-1), which bears some similarities to PECAM-1 in its cytoplasmic tail, which contains ITIM domains, and its capacity to recruit SHP-1 and SHP-2, have been shown to negatively regulate platelet thrombus formation in vitro and in vivo [137, 139142]. Interestingly, platelets also express junctional adhesion molecule-A (JAM-A) [143] and endothelial cell-specific adhesion molecule (ESAM) [144, 145], which belongs to the cortical thymocyte marker of Xenopus (CTX) family of the immunoglobulin superfamily.…”
Section: Integrin αIibβ3 Outside-in Signalingmentioning
confidence: 99%
“…In platelets, Shp2 inhibits pathways responsible for late outside-in signaling (e.g., the phosphorylation of Akt and ERKs) but has no effects on pathways responsible for early outside-in signaling (e.g., those mediated by the thrombin receptor), like Src phosphorylation. 22 However, the inhibitory effect of Shp2 by ERKs had not been previously described in platelets, although the in vitro phosphorylation of Shp2 by ERKs was shown to inhibit its phosphatase activity. 24 The regulation of C3G by the ERK-Shp2 axis is supported by the observation that C3G and Shp2 colocalize and that this colocalization is maximal under conditions of ERK inhibition.…”
Section: Discussionmentioning
confidence: 96%
“…20 In fact, the Shp1 and Shp2 phosphatases are major regulators of megakaryopoiesis, thrombopoiesis, and platelet function. 21 Recent studies showed an increase in the phosphorylation levels of ERKs in Shp2 −/− platelets, 21,22 suggesting the negative role of Shp2 in ERK activation. However, in other hematopoietic cells, Shp2 acts as a positive regulator of the Ras-ERK pathway downstream of cytokines and RTK receptors.…”
Section: Introductionmentioning
confidence: 99%